Duplicate Detection and Audio Thumbnails with Audio Fingerprinting - Burges, Christopher J.C.; Plastina, Dan; Platt, John; Renshaw, Erin; Malvar, Henrique S.; Burges, Chris J.C.; Malvar, Henrique S. (2004)
Audio fingerprinting is a powerful tool for identifying either streaming or file-based audio, using a database of fingerprints. This paper presents two new applications: duplicate detection, whose goal is to identify duplicate audio clips in a set, even if they differ in compression quality or duration, and thumbnail generation, which aims at providing a representative short clip of a music track. Each application is self-contained in that it does not require an external database of fingerprints. Thanks to the robustness of the fingerprinting engine, both applications perform well.